The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3892/ijo.2023.5563
|View full text |Cite
|
Sign up to set email alerts
|

Tumour follower cells: A novel driver of leader cells in collective invasion (Review)

Xiao-Chen Wang,
Ya-Ling Tang,
Xin-Hua Liang

Abstract: Collective cellular invasion in malignant tumours is typically characterized by the cooperative migration of multiple cells in close proximity to each other. Follower cells are led away from the tumour by specialized leader cells, and both cell populations play a crucial role in collective invasion. Follower cells form the main body of the migration system and depend on intercellular contact for migration, whereas leader cells indicate the direction for the entire cell population. Although collective invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 199 publications
(299 reference statements)
0
1
0
Order By: Relevance
“…Several studies have shown that the contri- bution of the follower cells to the migrating clusters goes beyond simply being dragged along passively. 2,13,30 During the migration of zebrafish polster cells, follower cells guide their migration by pulling the leader cells from behind through E-cadherin/a-catenin mechanotransduction. 31 Another work shows that followers push the leader cells during the migration of posterior lateral line primordium (PLLp) migrating within the zebrafish embryo.…”
Section: Papermentioning
confidence: 99%
“…Several studies have shown that the contri- bution of the follower cells to the migrating clusters goes beyond simply being dragged along passively. 2,13,30 During the migration of zebrafish polster cells, follower cells guide their migration by pulling the leader cells from behind through E-cadherin/a-catenin mechanotransduction. 31 Another work shows that followers push the leader cells during the migration of posterior lateral line primordium (PLLp) migrating within the zebrafish embryo.…”
Section: Papermentioning
confidence: 99%